E-Service Quality Klaim Jaminan Hari Tua (JHT) Melalui Aplikasi JMO Pada BPJS Ketenagakerjaan Cabang Cikokol Kota Tangerang - Yuniarti, Nuke; Hilman, Hilman; Utami, Pri (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
The advancement of digital public services prompted BPJS Ketenagakerjaan to launch the Jamsostek Mobile (JMO) application to streamline the Old-Age Security (JHT) claim process. However, implementation challenges persist specifically, data update failures that force participants to visit the office in person, thereby affecting the quality of electronic services. This study aims to analyze the e-service quality of JHT claims via the JMO application at the BPJS Ketenagakerjaan Cikokol Branch, Tangerang City. A qualitative method was employed, utilizing a descriptive approach and a post-positivist paradigm. Data were gathered through observation, in-depth interviews, and document analysis involving the Head of the Service Division, service staff, and JMO users; the data were subsequently analyzed through stages of reduction, presentation, and conclusion drawing. The findings indicate that the electronic service quality of the JMO application is not yet fully optimal. While aspects such as web design, trust, and personalization have enhanced user convenience, the aspects of reliability and responsiveness face obstacles including data update failures, system disruptions, and ineffective complaint handling esulting in some participants still needing to access services in person at the office. The study concludes that improving system reliability, accelerating responses to complaints, and optimizing digital services are essential to enhancing service effectiveness and participant satisfaction at BPJS Ketenagakerjaan.